Interactive Planning as Part of a Territorial Strategy to Develop Tourism Sites - RAMIREZ-ASIS, Edwin; HAMID, Abu Bakar Bin Abdul; ZAIN, Nor Hazila Binti Mohd; RAZA, Mohsin; RODRIGUEZ-KONG, Jose; ESPINOZA-REQUEJO, Cinthy (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).20, 2023)
Using the Callejón de Huaylas region as a case study, this article analyzes the role of interactive planning in the design of tourism areas from a territorial perspective. To begin tackling the complexity of the Callejón de Huaylas region, we chose degrees of municipal intervention in planning and the units of analysis for the questionnaire, and practices of participatory planning. This study is of a cross-sectional, non-experimental, descriptive design. As its instrument, a web-based questionnaire was provided by the out-of-the-ordinary circumstance, verified by a panel of 5 experts, and sent to a sample of 38 agents involved in direct and indirect roles in interactive planning for tourism places. In the end, it was found that the Callejón de Huaylas neighborhood benefits from a direct connection between the participatory planning procedures and the territorial planning strategy in the creation of tourism places.